Riforma agraria, bonifica e territorializzazione nelle Maremme toscane; alcuni spunti dall’archivio storico dell’Ente Maremma (1951-1965) - Gabellieri, Nicola (Scienze del Territorio, 2017)
This paper deals with the topic of the Agrarian reform in southern Tuscany (1951-1965) using a territorial history approach; that is, it focuses on the reshaping of local society, economy and environments due to a national process as the Reform, it highlights the importance of discontinuities in territorialisation trends. Methodologically, the use of a local approach allows a better understanding and depiction of social actors and past practices, avoiding the decontextualisation of places and historical processes. The first section of the paper presents some discussion topics emerging from an analysis of the historical archives of the public body competent for the Reform in Maremma; the second section presents a first hypothesis for a history of the Agrarian reform as a moment of requalification of environmental resources – changes in ownership, access and use – using water as a case study.  Finally, the paper highlights how the relations among social actors, environmental resources and territorial projects have been – and still are – a key point in territorialisation processes.